Aesthetics in breast conserving therapy: do objectively measured results match patients’ evaluations? - Heil, Jörg; Dahlkamp, Julia; Golatta, Michael; Rom, Joachim; Domschke, Christoph; Rauch, Geraldine; Sohn, Christof (Annals of surgical oncology, 2011)
To analyze the relationship of objective and subjective evaluation tools of breast aesthetics, we compare the results of the BCCT.core (breast cancer conservative treatment.cosmetic results) software, a semiautomated objective symmetry evaluation tool, with those of the Aesthetic Status of the BCTOS (Breast Cancer Treatment Outcome Scale) patient questionnaire.